The Hercules satellite: a stellar stream in the Milky Way halo? - Martin, Nicolas F.; Jin, Shoko (The astrophysical journal, 2010)
We investigate the possibility that the recently discovered Hercules Milky Way (MW) satellite is in fact a stellar stream in formation, thereby explaining its very elongated shape with an axis ratio of 3:1. Under the assumption that Hercules is a stellar stream and that its stars are flowing along the orbit of its progenitor, we find an orbit that would have recently brought the system close enough to the MW to induce its disruption and transformation from a bound dwarf galaxy into a stellar stream.